2012
DOI: 10.1136/archdischild-2011-301494
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in children admitted to paediatric intensive care: Table 1

Abstract: In contrast with current adult UK practice, tracheostomy for children admitted to intensive care is infrequent, performed late following admission and usually surgical. Practice varies significantly. The death rate for children having a tracheostomy performed was not significantly higher than for children admitted to PICU who did not undergo tracheostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
83
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 7 publications
13
83
0
6
Order By: Relevance
“…In addition, the rates of complication of the 2 methods in our series were similar, and no serious complications were encountered in either group during this study period, underscoring the rarity of serious complications from this procedure regardless of method. In light of equal efficacy, the only (1); other revision surgery included scar revision (11), endoscopic removal of granuloma (2), and tracheoplasty with graft to alleviate stenosis (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the rates of complication of the 2 methods in our series were similar, and no serious complications were encountered in either group during this study period, underscoring the rarity of serious complications from this procedure regardless of method. In light of equal efficacy, the only (1); other revision surgery included scar revision (11), endoscopic removal of granuloma (2), and tracheoplasty with graft to alleviate stenosis (1).…”
Section: Discussionmentioning
confidence: 99%
“…c Revision methods included cautery(2), and excision with primary closure (1); other revision surgery included endoscopic removal of granuloma (1). d Revision methods included excision with primary closure (5), excision with secondary intention(5), and cautery…”
mentioning
confidence: 99%
“…6,10,14 Reports have also indicated that the mortality rate among pediatric subjects with CHD and a tracheostomy ranges from 18.7% 6 to 52%. 20 In this study, we report a mortality rate of 43.1% for infants with CHD undergoing tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10][11][12] However, most studies have focused on the indications for tracheostomy, the subsequent outcomes, or resource utilization. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] Data are scant regarding the epidemiological risk factors for tracheostomy in CHD, and there have been no large-scale population-based studies. Furthermore, among infants with CHD requiring a tracheostomy, previous studies have failed to investigate either the overall mortality risk or the mortality risk stratified by a follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…A study to determine the current practice and opinions of paediatric intensivists in Canada reported an 81% response rate and showed that tracheostomy is rarely performed among ventilated children in Canada (rate <1.5%), although 51% of the responders believe that it is underutilised 2. The article by Wood et al in this issue reports on the current practice in PICUs in the UK 3. Tracheostomies are performed at a similar rate in children in the UK (only 2% of all PICU admissions over the 5-year period), and this is performed much less frequently than in adult practice.…”
mentioning
confidence: 99%